If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -66 + -10x = 7x + 19 Reorder the terms: -66 + -10x = 19 + 7x Solving -66 + -10x = 19 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -66 + -10x + -7x = 19 + 7x + -7x Combine like terms: -10x + -7x = -17x -66 + -17x = 19 + 7x + -7x Combine like terms: 7x + -7x = 0 -66 + -17x = 19 + 0 -66 + -17x = 19 Add '66' to each side of the equation. -66 + 66 + -17x = 19 + 66 Combine like terms: -66 + 66 = 0 0 + -17x = 19 + 66 -17x = 19 + 66 Combine like terms: 19 + 66 = 85 -17x = 85 Divide each side by '-17'. x = -5 Simplifying x = -5
| 5(m+2)=-4m-8 | | 107-5x=3x+11 | | 107-53=3x+11 | | f(-2)=-x^3+2x^2+x-1 | | 88-3x=9x+16 | | -2y=14-3x | | 5+3x=11+3x | | x=-5y+33 | | 5(m+2)=-4-8 | | 8x-22=4x+2 | | x^4+9x^2+20=0 | | 3y-10x=34 | | -4y-5x=-27 | | 4x+20=2x | | x^2-6x+58=0 | | (2x+3)(x-1)=0 | | (x+3)(x-2)=0 | | -2y-3=15 | | -2y-10=2 | | -9x-2=-38 | | -10y-1=99 | | -4x+5=17 | | 6b-5=4b+9 | | 8x-4=-12 | | -4y+5=9 | | -5x+9=54 | | 1y-4=4 | | -5y+7=47 | | -1x+2=11 | | x^2-y^2= | | -8x+9=1 | | -8y+8=88 |